2019
DOI: 10.1029/2018jc014537
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Variations in the Surface Upwelling off Northeastern Taiwan Observed via Satellite Data

Abstract: Short‐term biweekly variations in the surface upwelling off northeastern Taiwan are well documented. However, due to limitations in the spatiotemporal resolution and coverage of the observed data, the lifecycle and associated dynamics are poorly understood. In this study, a gradient‐based edge detection algorithm is proposed to detect the surface upwelling. The sea surface temperature data of geostationary satellite Himawari‐8 were used to explore a complete short‐term process as a case study. The evolution wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Cold domes mixed with China's and/or Taiwan's coastal currents exhibit only the decaying stage. We examined and plotted the time series for the GOCI chlorophyll-a data collected at the same time (Figure 9) as the Himawari-8 SST data (18-28 July 2016) time series presented in Figure 2 from Yin and Huang [53] and compared them. Although optical observation from space is typically blocked by clouds, the GOCI operating in a geostationary orbit can make eight observations every day and collect more valid images.…”
Section: Spatial Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cold domes mixed with China's and/or Taiwan's coastal currents exhibit only the decaying stage. We examined and plotted the time series for the GOCI chlorophyll-a data collected at the same time (Figure 9) as the Himawari-8 SST data (18-28 July 2016) time series presented in Figure 2 from Yin and Huang [53] and compared them. Although optical observation from space is typically blocked by clouds, the GOCI operating in a geostationary orbit can make eight observations every day and collect more valid images.…”
Section: Spatial Variationsmentioning
confidence: 99%
“…The results show that the cold dome in the UZONT indeed exhibited an enhancing stage followed by a decaying stage from the 18th of July to the 3rd of August 2016. However, this cold dome was not formed purely Yin and Huang [53] have also pointed out the difficulty associated with using only a few observations to identify whether the cold dome in the UZONT is formed purely by the local upwelling flow or is a mixture of China and/or Taiwan coastal currents. They suggested that, judging from the time series of observations of the cold domes formed purely by the local upwelling flow, they exhibit an enhancing stage followed by a decaying stage.…”
Section: Spatial Variationsmentioning
confidence: 99%
“…Numerous studies have been focused on the offshore upwelling to the Northeast of Taiwan, which is associated with a cyclonic cold dome [7][8][9][10]. Little literature, however, has indicated the existence of coastal upwelling along the Taiwan east coast.…”
Section: Introductionmentioning
confidence: 99%
“…Remotely sensed SST data have often been used to detect and map upwelling that exhibits local SST anomaly on the sea surface [4,9,10,15,16]. A coastal upwelling event often develops rapidly after a distinct onset and lasts from several days to some weeks, depending on the local condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation